MISYKÂT AL-ANWÂR KARYA AL-GHAZALI: SEKELUMIT CATATAN KONTROVERSI DAN TEOLOGI PENCERAHAN SUFISTIKNYA - Sopu, Salahuddin (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2016)
Misykât Al-Anwâr Al-Ghazali’s Work: Few Controversial Notes and Sufistic Enlightenment Theology. This paper attempts to discuss the book Misykât alAnwâr as the other side of a theological and philosophical Sufism of Al-Ghazali. Different than the Ihya ‘Ulum al-Din and his other works, Misykât alAnwâr featuringtheological and philosophical sufism in the high level. In this book, it is similar to the doctrine of Wahdat al-wujûd. Introducing the doctrine that there is no existing in this universe except Allah, because the form of everything other than Him is a shadow or comes from him. Although the book is thin and small, experts aligned this book with the magnum opus books of the sufis such as Futuhat al-Makkiyah by Ibn ‘Arabi, Matsnawi by Maulana Rumi, al-Hikam by Ibn Athaillah and others. Even this book became a milestone in the development of metaphysics of light by thinker after Al-Ghazali.